Биология пәнінде жобалап оқыту технологиясын қолданудың тиімділігі - Оразымбетова, Б.Б. (My University, 2016)
Modern society makes high demands not only to the level of knowledge of pupils, but also to the ability to work independently, the ability to address the problem. One of the possible ways to achieve these goals, students ' project activity. The project method of education awakens the student to demonstrate intellectual abilities, moral and communicative qualities, to demonstrate proficiency in the knowledge and study skills, goal setting, the ability to self-education and self-organization
Keywords: project; functionality; technology; development